Measuring the Prospective Efficiency Gains from Restructuring in Mergers and Acquisitions - Andanika, Andanika (Advances in Management & Financial Reporting, 2024)
Purpose: This study investigates the key factors influencing post-merger integration (PMI) success in mergers and acquisitions (M&A), focusing on internal organizational dynamics, external environmental conditions, and digital technology adoption. Research Design and Methodology: A systematic literature review synthesizes existing research on M&A transactions, organizational behavior, leadership, technology adoption, and regulatory compliance to analyze PMI challenges and success determinants. Findings and Discussion: The findings highlight that proactive leadership, effective communication, and transparent decision-making are crucial in fostering organizational cohesion and reducing resistance to change. Additionally, digital technology significantly enhances operational efficiency and drives value creation in the post-merger phase. Implications: The study underscores the need for a holistic and strategic approach to PMI, ensuring that internal and external factors are effectively managed. These insights contribute to the academic discourse on M&A by providing practical recommendations for corporate leaders, policymakers, and researchers to enhance PMI outcomes. Future research should explore industry-specific integration challenges and the evolving role of digitalization in optimizing M&A success.